Correlation between the APOE ε4 genotype, lifestyle habits, and cognitive deficits in Chinese adults over 60: a cross-sectional analysis in China - Li, Wei; Wang, XiaoLiang; Sun, Lin; Yue, Ling; Xiao, Shifu (Frontiers in Public Health, 2024)
IntroductionApolipoprotein E (APOE) epsilon 4 is regarded as the most significant genetic contributor linked to mild cognitive impairment (MCI) and Alzheimer’s disease (AD). Daily life elements might also influence cognitive abilities to some extent. This research aimed to investigate whether carrying APOE ε4 alters the effects of lifestyle on cognitive ability.MethodsThe research included 1871 senior community members with APOE gene data, all participating in clinical, neuropsychological, and daily living factor assessments. Based on their APOE ε4 status, they were categorized into two groups: the APOE ε4 group (n = 362) and the non-APOE ε4 group (n = 1,509). Subsequently, a multivariate logistic regression analysis was employed to investigate the link between cognitive deficits and APOE ε4, along with lifestyle patterns.ResultsOur research revealed a reduced incidence of MCI (OR = 0.745, 95% CI: 0.587–0.945, p = 0.015) and dementia (OR = 0.422, 95% CI: 0.259–0.688, p = 0.001) in the non-APOE ε4 carriers. Furthermore, the general linear regression analysis revealed a notable interplay between APOE ε4 and sleep disturbances, potentially impacting cognitive deterioration together (F = 6.817, p = 0.001).ConclusionsThe research indicates that possessing APOE ε4 alters the impact of everyday life factors on cognitive decline. In addition, there is a significant interaction between APOE ε4 and sleep disorders, which may jointly lead to the appearance of cognitive impairment.